Comparison of the Safety and Efficacy of Laparoscopic Left Lateral Hepatectomy and Open Left Lateral Hepatectomy for Hepatolithiasis: A Meta-Analysis - Wang, Xiaoji; Chen, Ai; Fu, Qiurong; Cai, Chunping (Frontiers in Surgery, 2021)
Background: Intrahepatic duct (IHD) stones, also known as hepatolithiasis, refers to any intrahepatic stones of the left and right hepatic ducts. It is a benign biliary tract disease with a high recurrence rate, with many complications, and difficulty in radical cure. The aim of this review and meta-analysis is to compare the safety and efficacy of the laparoscopic left lateral hepatectomy (LLLH) and open left lateral hepatectomy (OLLH) for IHD stones. Methods: Pubmed, Embase, Cochrane, WangFang Data, and China National Knowledge Infrastructure were searched for randomized controlled trials (RCTs) regarding the comparison of LLLH and OLLH in the treatment of hepatolithiasis. Standard mean difference (SMD), odds ratio (OR), and 95% CI were calculated using the random-effects model or fixed-effects model according to the heterogeneity between studies. Results: From January 01, 2001 to May 30, 2021, 1,056 articles were retrieved, but only 13 articles were finally included for the meta-analysis. The results showed that compared to the OLLH group, LLLH resulted in smaller surgical incision, less intraoperative blood loss, faster postoperative recovery, and fewer postoperative complications (surgical incision: SMD = −3.76, 95% CI: −5.40, −2.12; intraoperative blood loss: SMD = −0.95, 95% CI: −1.69, −0.21; length of hospital stay: SMD = −1.56, 95% CI: −2.37, −0.75; postoperative complications: OR = 0.45, 95% CI: 0.26, 0.78). Conclusions: In the treatment of hepatolithiasis, compared with OLLH, LLLH has the advantages of less intraoperative blood loss, smaller incisions, less postoperative complications, shorter hospital stay, shorter time to first postoperative exhaust, and postoperative ambulation, and rapid postoperative recovery.